Important alien and potential native invasive insect pests of key fruit trees in Sub-Saharan Africa: advances in sustainable pre- and post-harvest management approaches - Shepard Ndlela; Saliou Niassy; Samira A. Mohamed (CABI Agriculture and Bioscience)
Abstract Fruit production in Sub-Saharan Africa is of paramount importance both socially and economically. Millions of farmers derive livelihoods from mango, avocado, citrus, cashew, and coconut farming, but native and alien invasive species constrain production The region’s capacity to contain invasives is weak due to the absence of national and institutional support systems for early detection, containment, eradication, or management of the pests. Climate change is expected to play a huge role in the influx of more alien invasive species and the shift of ecological requirements of some native species. Though a fair share of pre-and post-management pest management techniques for several insect pests has been developed, adoption and adaptation of the options are limited. Data on economic and social implications are largely lacking, making it challenging to implement informed policy decisions. The existence of the “Strategy for Managing Invasive Species in Africa 2021–2030” promises a paradigm shift in the management of invasives, from reactive thinking to coordinated proactive approaches. The uncoordinated deployment of management measures in the region and the lack of funding, play a negative role in managing the pests effectively. Prospects for enhanced future research are wide, and efforts are currently being channeled to Area-Wide-Integrated Pest Management in a bottom-up approach with stakeholders owning the process. Participatory development of technologies is also taking centre stage, paving the way for increased adoption and adaptation. Postharvest technologies promise to provide the adequate phytosanitary assurance required by countries importing fruit from Sub-Saharan Africa.